Perancangan Model Laporan Keuangan Berdasarkan SAK EMKM Berbasis Microsoft Excel (Studi Kasus Pada Kelompok Usaha Menengah Jasa Ekspedisi Pupuk Kujang - Kab. Karawang) - Muhammad Yudha Pratama; Lili Indrawati (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
One of the tools to measure company performance is financial reports. The financial reports that are made must comply with existing standards, such as SAK EMKM as a specific standard for MSME actors. The process of preparing financial reports for MSMEs must be familiar and easy to do. The tool that is familiar to MSMEs is Microsoft Excel. This study aims to assist medium-sized businesses in cleaver fertilizer expedition, particularly in the Karawang area in preparing financial reports. The financial statements are prepared by optimizing the existing functions in Microsoft Excel. The methods used in this research are qualitative and quantitative. Data obtained from documentation and direct interviews. The result of this research is the design of financial statement model based on Microsoft Excel.